El fanzine argentino Resistencia Contra-archivo de una interseccionalidad punk - Karakilinc, Hasan (Diálogos Latinoamericanos, 2023)
The fanzine Resistencia, began to be published in Buenos Aires in December 1984, a year after Argentina’s return to democracy. The fanzine served as the main tool for spreading punk radicality for over a decade alongside pamphlets and the lyrical corpus produced by the Buenos Aires punk scene’s participants. The relevance of Resistencia, as a genuine cultural counter-archive, lies in its critical content and proposals for sociopolitical change framed by radical discourses. Stemming from the raw social nihilism inherited from its early phase during the military dictatorship, the punk scene becomes increasingly politicized through discourses fueled by anarchism. In addition to criticizing repressive practices that linger from the dictatorship, Resistencia progressively sought to articulate a focus on intersectional struggle, intertwining feminism, anti-racism, anti-homophobia, environmentalism, and anti-speciesism to provide readers with a more holistic view of systems of domination. Based on an analysis of the fanzine Resistencia, this article highlights the processes of ideological transformation and the embodiment of intersectional discourses in a context marked by the resurgence of democracy and the ghosts of the military dictatorship.